Variations in boldness, behavioural and physiological traits of an endangered and a common hylid species from Korea. Issue 6 (2nd November 2018) - Borzée, Amaël; Yu, Ai-Yun; Jang, Yikweon
Abstract : Animal populations with narrow distribution ranges due to recent constrictions are predicted to be physiologically and evolutionarily less fit than their counterparts with wider distributions. In anurans, muscle mass and body size are generally correlated with locomotor and physiological performances. These, in turn, may be representatives of species-specific strategies such as predator avoidance, exploration, habitat use, and dispersal. We conducted behavioural experiments and field observations to assess the differences in physiological capacity, exploratory behaviour, and response delay between the endangered Dryophytes suweonensis and the widespread D. japonicus . The complementary genetic analyses revealed a lower genetic diversity in D. suweonensis than in D. japonicus . Despite its smaller size, D. suweonensis displayed a significantly larger mass for locomotor muscles, but a longer delay for responses to stimulus and a lower endurance than D. japonicus . The combined lower cognitive delay for behavioural responses of D. suweonensis and the better endurance of D. japonicus make the later species more fit to its environment, allowing for faster escape and wider dispersal capabilities. Our results therefore highlight the correlation between the endangered D. suweonensis with a narrow ranges and depressed boldness, in comparison to the widespread and closely related D. japonicus . These results are clade specific, but open a potential new line of research into species decline.